Geographic Reference Income and the Subjective Wellbeing of Australians - Phelps, Christopher; Harris, Mark; Rowley, Steven; ViforJ, Rachel Ong; Wood, Gavin (2023)
In this paper panel data is used to estimate the relationship between geographic reference income and subjective wellbeing in Australia. Recent cross-sectional US-based studies suggest that the income of other people in a neighbourhood—geographic reference income—impacts on individual wellbeing but is mediated by geographic scale. On controlling for a household’s own income, subjective wellbeing is raised by neighbourhood income and lowered by region-wide income. However, these findings could be driven by the self-selection of innately happy or unhappy individuals into higher-income areas. This study’s methodology takes advantage of panel-data modelling to show that unobserved individual heterogeneity is in fact correlated with reference income, but on curbing its impacts through the inclusion of fixed-effects we find that there is still a positive relationship between reference income and subjective wellbeing at the neighbourhood level. However, we detect no relationship at the region-wide level. Additionally, the subjective wellbeing relationship is the same no matter an individual’s rank in the distribution of incomes within an area. The neighbourhood wellbeing relationship has implications for policies addressing residential segregation and social mixing.